CAFF Circumpolar Biodiversity Monitoring Program Report No.16 - Arctic Marine Mammal Monitoring Plan - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (CAFF, 2009)
Arctic Council's Conservation of Arctic Flora and Fauna Working Group (CAFF) Report: Arctic Marin Mammal Monitoring Strategy